Protamine and other proteins in sperm and seminal plasma as molecular markers of bull fertility - Pardede, Berlin Pandapotan (Vet World, 2020)
Fertility is the most important aspect in the efforts to increase livestock populations. Protamine and various proteins in sperm and seminal plasma are the results of the molecular analysis which can be used as a marker of fertility. Each of the proteins plays an important role in the normal function of sperm, starting from the formation of sperm structure, motility, capacitation, cell protection, acrosome reactions, successful fertilization, egg activation, and embryonic development. Finally, these molecular components can be a marker of fertility and can help to diagnose the cases of infertility/subfertility in livestock in the field.